Signalling with Many Signals - Engers, Maxim (Econometrica, 1987)
This paper examines a market with asymmetric information where there are many signals available and where both the costs of signaling and the product value may depend on many privately known characteristics. Under a weak condition on the relationship between the marginal cost of increasing the signals and the product value, a separating set exists whereby the value of every seller's product is inferred from the seller's optimal choice of signals. The separating set constructed is Pareto dominant and corresponds to recently proposed equilibrium notions in signaling and screening models. Copyright 1987 by The Econometric Society.